2023
DOI: 10.1111/jvim.16809
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25‐hydroxyvitamin D, vitamin D receptor, and vitamin D binding protein concentrations in dogs with acute pancreatitis compared to healthy control dogs

Abstract: BackgroundPrevious studies have documented vitamin D imbalance in dogs with acute pancreatitis (AP), but no studies have investigated serum vitamin D receptor (VDR) and vitamin D‐binding protein (VDBP) concentrations.ObjectivesCompare serum 25‐hydroxyvitamin D (25[OH]D), VDR, and VDBP concentrations in healthy dogs and dogs with AP and identify correlations between these concentrations with ionized calcium, C‐reactive protein (CRP), and canine‐specific pancreatic lipase (Spec cPL) concentrations.AnimalsTwenty‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…VDR expression is regulated transcriptionally by various molecules, including 1,25(OH) 2 D, parathyroid hormone, and fibroblast growth factor 23 ( 29 , 30 ), and differentially regulated in each tissue; for example, treatment with 1,25(OH) 2 D enhanced the VDR expression in kidneys but not in the intestine ( 30 ). Although the circulating levels of 1,25(OH) 2 D in dogs with pancreatitis were not determined, a decreased 25(OH)D concentration was reported in dogs with pancreatitis ( 15 , 31 ) and might have negatively regulated VDR transcription in inflamed pancreases. It is unclear whether the VDR transcription in the island of Langerhans is more affected than that in the pancreatic ducts and acini by various factors such as 1,25(OH) 2 D. Further studies on the effect of circulating 1,25(OH) 2 D levels on VDR expression in each part of the pancreas (ducts, acini, and islets of Langerhans) would be beneficial to identify the pathophysiology of VDR disruption in inflamed canine pancreases.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…VDR expression is regulated transcriptionally by various molecules, including 1,25(OH) 2 D, parathyroid hormone, and fibroblast growth factor 23 ( 29 , 30 ), and differentially regulated in each tissue; for example, treatment with 1,25(OH) 2 D enhanced the VDR expression in kidneys but not in the intestine ( 30 ). Although the circulating levels of 1,25(OH) 2 D in dogs with pancreatitis were not determined, a decreased 25(OH)D concentration was reported in dogs with pancreatitis ( 15 , 31 ) and might have negatively regulated VDR transcription in inflamed pancreases. It is unclear whether the VDR transcription in the island of Langerhans is more affected than that in the pancreatic ducts and acini by various factors such as 1,25(OH) 2 D. Further studies on the effect of circulating 1,25(OH) 2 D levels on VDR expression in each part of the pancreas (ducts, acini, and islets of Langerhans) would be beneficial to identify the pathophysiology of VDR disruption in inflamed canine pancreases.…”
Section: Discussionmentioning
confidence: 96%
“…A previous study showed that the serum VDR concentration is decreased in dogs with acute pancreatitis; however, it was unclear which organs contributed to the low serum VDR concentration ( 15 ). Although the present study included only pancreatic tissues and not others where VDR is highly expressed, such as the kidneys and gastrointestinal tract ( 25–27 ), it was shown that VDR expression was decreased in the inflamed pancreatic tissue, supporting that this could contribute to the low serum VDR concentrations in dogs with pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations